Answer:
x = - 7
Step-by-step explanation:
8x - 2 = -9 + 7x (add 2 to both sides)
8x - 2 + 2 = -9 + 7x + 2
8x = 7x - 7 (subtract 7x from both sides)
8x - 7x = 7x - 7 - 7x
x = - 7
Answer:
y=6
Step-by-step explanation:
7y+6=18-5y
-5y, -6
2y=12
y=6
Answer x/3 -(-2)= 16
X/3+ 2=16
X/3=16-2
X/3=14
X= 14x3=42
Step-by-step explanation:
3 (2x + 4y - y) Combine like terms (4y and -y)
3 (2x + 3y) Use the Distributive Property [(3 · 2x) + (3 · 3y)]
6x + 9y
Answer:
First answer is 14
Second answer is 25
Step-by-step explanation:
Median is the middle ( 1 2 3 4 5 the median would be 3)
You start at 2 and end at 27
List all the numbers from 2 to 27 and come from both ends until you get to the middle number(s)
In this case there are two 14 & 15
14+15=29 29÷2=14.5
Since there are no decimal answers you are left with 14
Range you take the two end numbers and subtract them (27 & 2)
27-2=25
Hopefully this helps!